ENGAGEMENT, DELIBERATION AND INFORMATION: HOW STUDENTS THINK ABOUT DEMOCRACY - Brasil, Marina Valentim (2022)
This work sought to understand the way high school students from a public school in Porto Alegre (RS) understand the concept of democracy, based on the premise that this notion is necessary for an effective civic engagement and could also indicate  the role of education in public life that has taken place in our context. This is a qualitative and exploratory research, being part of a larger study. A school was contacted in May 2018, and 197 high school students participated in the survey. The results of the analysis of the students' answers to the question “What is democracy?” will be presented. As the method of analysis, the Thematic Analysis was used. Based on the responses of the participants, five thematic axes were generated, in which the ideas about democracy seem to show an important distance from the theme of democracy. It is argued that even with several mobilization resources guaranteed nowadays and pro-democracy postures being evident, the biggest barrier to an effective exercise of public life may still be the absence of opportunity to political instrumentalization, through more information and the defense of the democracy values . Therefore, we lack institutional guarantees in an aspect firmly evidenced as indispensable by the academic literature: the guarantee of being politically educated. It is argued that the most deficient aspect for active youth citizenship is the guarantee of formal spaces so that it can be built, and that this must occur within schools.